AN ANALYSIS OF THE INTENSITY OF VEHICLE USE USING THE EXAMPLE OF THE POLISH MAIL COMPANY - Komsta, Henryk; Krzywonos, Leszek; Winiarski, Grzegorz (Doprava a spoje, 2011)
Intensity of vehicle use is one of the most important parameters of vehicle operation. The intensity of use affects vehicle life, the costs and the profits from transportation services and other parameters of car operation. It is expressed as the number of kilometers traveled by a car within a specified period of time (day, month, or year). For that reason, analysis of data associated with the intensity of vehicle use may be instrumental in the evaluation of a given transport firm. The paper presents and discusses the results of statistical analyses of data related to the intensity of use of delivery trucks in the Polish Mail company in Lublin